Upaya Peningkatan Pengetahuan Tentang Menstruasi di SMP Negeri 1 Sadananya - Aditya Nurwahyuni; Herni Oktriani; Hani Monika; Hera Maulidiyah (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Menstruation is a physiological event for young women, in this case the reproductive hormones have started to work. This phase is one of the indicators of sexual maturity in adolescent girls. in which the discharge of blood, mucus, and cellular debris from the uterine lining is accompanied by periodic and cyclical shedding of the endometrium, beginning about 14 days after ovulation Objective: The goal of this Health Counseling is to add/increase participant's insight regarding the definition, hygiene, disorders during menstruation. Method: The method used is direct question and answer with random participants and fill out the pre-test and post-test sheets. Result: The results of the evaluation showed that the health education had been carried out properly in accordance with the results indicators and criteria on the observation sheet instrument. The observation sheet is based on five dimensions, namely timeliness and duration, participation, knowledge, job description and problem solving. The evaluation sheet is filled out by independent observers. Conclusion: Based on the evaluation results, health education activities to increase knowledge have been successful with individuals with indicators of timeliness and duration, participation, knowledge, job descriptions, and problem solving. In the discussion session, all participants were enthusiastic to ask questions and listen and understand what the speakers answered from what they asked. In the post-implementation evaluation session, participants answered what was asked without hesitation and answered the post-test sheet correctly. The results of the observations showed an increase in participants' knowledge. The pre-implementation evaluation showed that 3 out of 28 people gave responses to the questions given, could answer the questions correctly, but after health education, 11 out of 28 participants gave correct feedback. This shows a change in the status of knowledge before and before health education is carried out. suggestions for this activity need time management so that the counseling can be carried out according to the time specified in the SAP